Asymmetric Oxidative Mannich Reactions. Issue 3 (9th November 2020) - Rostoll‐Berenguer, Jaume; Blay, Gonzalo; Pedro, José R.; Vila, Carlos
Abstract: The asymmetric Mannich reaction is one of the most straightforward methodologies for the enantioselective synthesis of chiral amines. In general, asymmetric Mannich reactions involve the use of imines as electrophiles. However, in recent years, several asymmetric oxidative Mannich reactions have been reported using amines as electrophiles. This review provides an overview of these recent publications, including the different oxidants used and the scope and limitations of the different catalytic systems. Abstract :